Factors Determining the Choice of Innovation in Construction Enterprises in Poland - Aneta MADYDA (Communications of International Proceedings, 2021)
Polish enterprises, including construction, wanting to increase their attractiveness must look for and use new development factors. The following research hypothesis was assumed, which set the direction of research: thanks to the application of innovations, a building contractor can build a competitive advantage. The main goal of the conducted research was to identify the factors that decided about the implementation of innovations in Polish construction companies and those that could induce entrepreneurs to use them in the future. The results of the survey illustrate the direction and intensity of the direction of changes in the competitiveness of Polish construction companies.
Keywords: Inovation; Competitiveness; Enterprise; Construction Sector.